2015
DOI: 10.1155/2015/605325
|View full text |Cite
|
Sign up to set email alerts
|

Youssef’s Syndrome following Cesarean Section

Abstract: Youssef's syndrome is characterized by cyclic hematuria (menouria), absence of vaginal bleeding (amenorrhea), and urinary incontinence due to vesicouterine fistula (VUF), the least common of the urogynecological fistulas. Youssef's syndrome has a variable clinical presentation. A vesicouterine fistula is an abnormal pathway between the bladder and the uterus. The most common cause is lower segment Cesarean section. Conservative treatment may be appropriate in some cases, but surgery is the definitive treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 12 publications
1
34
0
2
Order By: Relevance
“…Two women had menouria only while11 had menouria with continuous involuntary leakage of urine. Although the complaint of menouria is consistent in our study, the presentation of vesicouterine syndrome has showed some variation from the triad described by Youssef as some patients present with involuntary leakage of urine and even normal menstruation depending on the level of the injury to the bladder [3,[6][7][8][9][10]. The cause of the urinary incontinence is the communication between the bladder and the uterine cavity allowing leaking of urine through the cervix into the vagina.…”
Section: Previous Cs No Previous Cs Totalsupporting
confidence: 76%
See 2 more Smart Citations
“…Two women had menouria only while11 had menouria with continuous involuntary leakage of urine. Although the complaint of menouria is consistent in our study, the presentation of vesicouterine syndrome has showed some variation from the triad described by Youssef as some patients present with involuntary leakage of urine and even normal menstruation depending on the level of the injury to the bladder [3,[6][7][8][9][10]. The cause of the urinary incontinence is the communication between the bladder and the uterine cavity allowing leaking of urine through the cervix into the vagina.…”
Section: Previous Cs No Previous Cs Totalsupporting
confidence: 76%
“…Hence thorough evaluation is necessary for diagnosis [8]. Some authors have indeed suggested that vesicouterine fistula should be suspected in any woman presenting with urinary incontinence even years after caesarean section [7,19].…”
Section: Previous Cs No Previous Cs Totalmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinpe and colleagues in 1908 reported the first case of VUF. 3 It is named after the Egyptian gynaecologist Abdel Fattah Youssef. Youssef in 1957 described the vesicouterine fistula with classical triad of urinary incontinence, cyclic haematuria (menouria) and amenorrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated caesarean section doubles the risk of VUF. 3 Other less common causes of VUF are dilatation and curettage, uterine rupture, placenta percreta, instrumental delivery, manual removal of placenta, obstructed labor. Other least frequent causes are migrated intrauterine contraceptive device, brachytherapy, inflammatory bowel disease, endometriosis, bladder tuberculosis and congenital lesions.…”
Section: Introductionmentioning
confidence: 99%